Program for climate-smart livestock systems. Country stocktake: Ethiopia - Thornton, Philip K.; Enahoro, Dolapo K.; Njiru, Nelly M.; Wijk, Mark T. van; Ashley, Laurie; Cramer, Laura K.; Ericksen, Polly J.; Graham, Michael (International Livestock Research Institute, 2019)
This is one of a series of documents that summarises information relating to the livestock sector in the three PCSL countries (Ethiopia, Kenya and Uganda). Prevailing livestock systems and their baseline performance in Ethiopia is summarised first, followed by a summary of what is known about the impacts of climate change on livestock production and livestock systems. Section 4 briefly summarises some recent research on adaptation and mitigation options for livestock systems in Ethiopia. Section 5 considers some of the work that has been done to date on projections for the livestock sector to the middle of the century. Section 6 considers the national livestock and climate change policy environment. The paper concludes with a consideration of system intervention points and major gaps in knowledge, to help guide project activities in Ethiopia.